Validation of Plastic Waste Pyrolysis Prototype Design Based on Used Oil Burner with A Simple Condensation System Using Software - Laiya, Moh Risman Nabuah; Prumanto, Denny; Komarudin, Komarudin (Greenation Research & Yayasan Global Resarch National, 2025)
Plastic waste is a serious environmental problem because it is difficult to decompose and its volume continues to increase. One potential solution is pyrolysis technology, a thermal decomposition process at high temperatures in the absence of oxygen that produces oil, gas, and solid residue. This study aims to validate the performance of simulation software in designing a prototype pyrolysis machine using a used oil burner with a simple condensation system through design, simulation, and experimental testing. A three-dimensional model was created using SolidWorks, while temperature distribution analysis was performed using ANSYS. The prototype was designed to process approximately 2 kg of PP and PET plastic at 300–500°C. Parameters analyzed included reactor temperature distribution, condenser temperature drop, and heating and cooling system performance. Both simulation and experimental results demonstrated good performance. The used oil burner produced stable heat, and the condensation system effectively converted steam to oil, demonstrating the prototype's potential for development into an efficient and economical small-scale pyrolysis machine.